2017
DOI: 10.3945/an.117.015941
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: An Extension of the STROBE Statement for Observational Studies in Nutritional Epidemiology (STROBE-nut): Explanation and Elaboration

Abstract: Nutritional epidemiology is an inherently complex and multifaceted research area. Dietary intake is a complex exposure and is challenging to describe and assess, and links between diet, health, and disease are difficult to ascertain. Consequently, adequate reporting is necessary to facilitate comprehension, interpretation, and generalizability of results and conclusions. The STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) statement is an international and collaborative initiative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 134 publications
0
31
0
Order By: Relevance
“…For the control (Word Document) tool, we used the relevant checklists of reporting guidelines and their E&E document which were downloaded from the relevant websites 22–25…”
Section: Methodsmentioning
confidence: 99%
“…For the control (Word Document) tool, we used the relevant checklists of reporting guidelines and their E&E document which were downloaded from the relevant websites 22–25…”
Section: Methodsmentioning
confidence: 99%
“…This study is reported according to the Strengthening the Reporting of Observational Studies in Epidemiology-Nutritional Epidemiology (STROBE-nut) guidelines [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study was carried out in two paths: as an education-based intervention design and a cross-sectional design. The study is reported according to the guidelines of reporting of observational and intervention studies of public health in nutritional epidemiology [ 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%